Model Pengembangan Ilmu Ekonomi Islam - Muhamad Muhamad (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
Economics as a science that deals with human behavior, will always develop according to the will of man himself. Thus, the need for establishing economic law that is following sharia and the real world that humans need, demands the need for continuous ijtihad. Considering that there have been considerable changes in the way people live after the industrial revolution, technological developments, and international material relations, a big world looks like a small country. Something that used to be normal, but recently turned a hundred and eighty degrees into something different. So this needs ijtihad. This research is qualitative research that describes the results of research in the form of a model for the development of Islamic Economics as a form of the researcher's contribution to the development of Islamic economics.According to Qardawi, two fields need ijtihad in recent times, namely finance and economics, and medicine. Because these two fields intersect directly in human life. In the development of Islamic economics, it is necessary to have a different model from the development model of economics in general.